KINEMATICS OF A REAR BODY OF A FLAT PLOWING PLOUGH WITH A TURNING SHAFT - Badalov Sunatullo Mamadiyevich; Salimov Behruz Xo‘jayor o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. In this paper, the kinematics of a tipping deck is investigated. The main types of palax movement are analyzed — turning, sliding and tipping. Using kinematic modeling, methods for determining the parameters of Pallas’s velocity and acceleration, and representing the trajectory of motion are considered. The physical properties of palax motion are also analyzed based on the graphical representation of motion, communication conditions, and equations of state. This topic plays an important role in the deep understanding of the motion of complex bodies in mechanics and engineering sciences.